Margins of safety can be lowered for supplemental copper, zinc, iron, and manganese in finishing diets without affecting growth performance - Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Finishing pig diets are commonly supplemented with copper, zinc, iron, and manganese with large margins of safety compared to those suggested by NRC requirements. In this study, pigs were fed a control diet that provided these minerals supplemented at concentrations similar to current KSU recommendations, diets containing 50 and 25% of the recommendation, or a combination of 50% of the recommendations until 145 lb and no added trace minerals from 145 lb until market. The trial used pigs from 100 lb until market weight at 265 lb. No differences in growth perfonnance or carcass characteristics were observed as a result of trace mineral supplementation. These results suggest that the margins of safety for copper, zinc, iron, and manganese can be lowered significantly in swine finishing diets.
Keywords: Swine; Finishing pigs; Performance; Copper; Zinc; Iron; Manganese